A General Framework for Studying Contests - Spencer Bastani; Thomas Giebe; Oliver Gürtler (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
We develop a general framework for studying contests, including the well-known models of Tullock(1980) and Lazear & Rosen (1981) as special cases. The contest outcome depends on playersâ efforts and skills, the latter being subject to symmetric uncertainty. The model is tractable, because asymmetric equilibrium exists under general assumptions regarding production technologies and skill distributions. Using a link between our contest model and expected utility theory, we are able to derive new comparative statics results regarding how the size and composition of contests affect equilibrium effort, showing how standard results can be overturned. We also discuss the robustness ofour results to changes in the information structure and the implications of our findings for the optimal design of teams.
Keywords: C72; D74; D81; J23; M51; 330; contest theory; symmetric equilibrium; heterogeneity; risk; stochastic dominance